Chemical Synthesis and Isolation of Trans‐Palmitoleic Acid (Trans‐C16:1 n‐7) Suitable for Nutritional Studies. Issue 6 (19th May 2020) - Guillocheau, Etienne; Drouin, Gaëtan; Catheline, Daniel; Orione, Clément; Legrand, Philippe; Rioux, Vincent
Abstract: Trans ‐palmitoleic acid ( trans ‐9 C16:1, or trans ‐C16:1 n‐7, TPA) is typically found in ruminant‐derived foods (milk and meat). Of note, previous epidemiological studies associated high levels of circulating TPA with a lower risk of type 2 diabetes and metabolic syndrome in humans. At the current time, TPA intakes in humans are ensured by ruminant‐derived foods. However, due to the very low commercial availability of TPA, there are no supplementation studies carried out so far. Therefore, the ability for dietary TPA to prevent type 2 diabetes and metabolic syndrome has never been experimentally assessed. Here, a method (among others) to get dozens of grams of pure TPA as ethyl ester, to perform dedicated supplementation studies, is reported. For that purpose, it starts from food sources containing high amounts of cis ‐palmitoleic acid ( cis ‐9 C16:1, or cis ‐C16:1 n‐7, CPA), dealing with fatty acids ethyl esters all along the experiment. CPA is purified with flash liquid chromatography, then submitted to a cis / trans isomerization step. Finally, TPA is separated from CPA by low‐temperature crystallization in methanol. The final product is fully characterized by 1 H and 13 C nuclear magnetic resonance spectrometry. It is possible to produce ≈70 g of 85%‐purity TPA suitable for nutritional studies. Practical Applications : The synthesized trans ‐palmitoleic acid may serve for supplementation (or nutritional) studies aiming at unravelling its physiological impacts suggested by epidemiological work. Depending on the amount of synthesized trans ‐palmitoleic acid, one may carry out nutritional studies on rodents or even on humans. Abstract : A method is described in this manuscript to get pure trans ‐palmitoleic acid ethyl ester in enough amounts to carry out nutritional studies. The dietary complement Provinal is used as a source of cis ‐palmitoleic acid, in combination with flash LC. Isomerization and large scale cis / trans fractionation were applied afterward.